STRATEGI PENGENALAN IBADAH PUASA RAMADHAN PADA ANAK USIA DINI DI PAUD AL-KAMAL JAMPANGTENGAH, KABUPATEN SUKABUMI - Irma Muti; Jimatul Arrobi; Resti Nurhabibah; Siti Wahyuni; Nia Audina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies for introducing Ramadan fasting to early childhood students at PAUD Al-Kamal Jampangtengah, Sukabumi Regency. A qualitative approach with a case study design was employed to gain an in-depth understanding of the implementation practices carried out by teachers and parents. The research subjects consisted of the principal, teachers, and parents selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings indicate that the introduction of fasting was implemented through gradual habituation, role modeling, educational play, storytelling, positive reinforcement, and collaboration between school and family. Contextual and non-coercive approaches positively contributed to children’s self-regulation, emotional stability, and internalization of religious values. This study proposes an integrative model combining pedagogical, social, emotional, and environmental dimensions as a systematic framework for early childhood religious character education. The model offers both conceptual and practical contributions for early childhood education institutions in designing developmentally appropriate Ramadan learning programs.